Advanced Periocular Basal Cell Carcinoma with Orbital Invasion: Update on Management and Treatment Advances - Alvaro Bengoa-González; Enrique Mencía-Gutiérrez; María Garrido; Elena Salvador; María-Dolores Lago-Llinás (Journal of Ophthalmology)
Purpose. Basal cell carcinoma (BCC) is the most frequent malignant periocular tumor. It is associated with exposure to ultraviolet radiation, and its incidence is gradually increasing. It may occasionally display more aggressive behavior and result in orbital or intracranial invasion. Mortality from periocular BBC with orbital invasion is very low, but the associated morbidity can be significant, from disfigurement to blindness. Traditionally, these cases have been treated with orbital exenteration or with radiotherapy (RT), but in recent years, hedgehog pathway inhibitors (HPIs) have emerged, are effective in more serious cases, and are used primarily or combined with surgery, changing our perspective on the management of these patients. Methods. We studied 24 cases of periocular BCC with orbital invasion, some primary and others recurrent, which were treated between 2011 and 2021 in the same hospital. All patients had clinical or radiological evidence of orbital invasion. Orbital exenteration was performed on 9/24 of the patients (1 received vismodegib after surgery), and 12/24 were treated, surgically preserving the eyeball, with 3 of them receiving adjuvant vismodegib. Three of the twenty-four patients were treated exclusively with vismodegib (Erivedge®, Genentech). Results. One patient died due to poor tumor evolution, but the rest evolved favorably and they have had no recurrences. Vismodegib was generally well tolerated, except for in one patient who discontinued treatment due to the side effects. Conclusions. In advanced BBC with orbital invasion, mutilating surgical treatments such as exenteration or potentially vision-threatening treatments such as RT remain as options. In recent years, however, very promising new medical therapies have emerged, such as HPI, which can be used effectively instead of surgery or in combination with it, preserving the eye and vision, which implies a new approach to treatment.